Formation and development of Kazakh children’s folklore - Baltymova M. R., Pangereyev A. S, (Opción, 2019)
This article is devoted to the problems of the formation and development of Kazakh children’s folklore via a comparative qualitative research method. As a result, during the period of activation of the publishing business, work was carried out on the systematic coverage of samples of oral folk literature, the traditional art of aitys folk poets in the country became more active. In conclusion, given that the features of folklore as a word associated with literature, folklore is a folk work, a national work, a work of art of the people orally.